Multiple substance use and associated factors in transgender women and travestis: findings from the TransOdara Study, Brazil - Jurema Corrêa da Mota; Sandro Sperandei; Raquel Brandini De Boni; Inês Dourado; Maria Amélia de Sousa Mascena Veras; Francisco Inácio Bastos (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective To estimate the prevalence of concomitant substance consumption and analyze associated risk factors in a non-probabilistic sample of the Brazilian population of transgender women and travestis. Methods A cross-sectional study was conducted with recruitment via respondent-driven sampling. The sample included transgender women and travestis residing in São Paulo, Porto Alegre, Salvador, Manaus, and Campo Grande, aged 18 years or older, between 2019 and 2021. The outcome was the concomitant use of licit and illicit substances. The association between sociodemographic/behavioral factors and the outcome was analyzed through Poisson regression with mixed effects. Adjusted prevalence ratios (confidence interval of 95% - 95%CI) were estimated. Results The prevalence in the last 12 months of multiple substance use was 49.3%, of which 65.5% were alcohol, 52.9% tobacco, and 40.1% marijuana. Transgender women and travestis who use multiple substances face more violence (1.71; 95%CI 1.14-2.55), unemployment (1.58; 95%CI 1.05-2.37) and pervasive unstable work status (1.52; 95%CI 1.08-2.14), transactional sex (1.51; 95%CI 1.21-1.88) which can be their sole option to make a living, and are aged 18 to 24 years (1.37; 95%CI 1.14-1.65). Conclusion The use of multiple substances may be an attempt to cope with distress and marginalization. Substance use has been associated with multiple harms and medical conditions. Comprehensive management and care should be provided, as defined by the key principles of the Brazilian Unified Health System. Health care should be integrated into structural interventions.